The Case of the Most Ancient Bone - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog., 2013)
Digging up trouble...Hank the Cowdog is on the case in his 50th mystery, and it's an extra long, laugh-out-loud adventure! When Hank gets invited - that is, invites himself - on an archaeological dig, all he can think about is impressing the head scientist's beautiful lady dog. But Hank's heart isn't the only thing that's about to get stolen! Can the Head of Ranch Security save an ancient buffalo bone from thieves who want to devour the precious artifact and have Hank for dessert?